Equity valuation and analysis with eVal - Lundholm, Russell James; Sloan, Richard G. (Boston : McGraw-Hill Irwin, 2007)
This book is to demystify the valuation process. It also provide plenty of advice on where to go to obtain the most relevant raw data, eVal is supplied with historical financial statement data for over 8,000 companies.
Includes index.
osa02/05/13
Loans
Keywords: Corporations -- Valuation; Business enterprises -- Valuation; Stock price forecasting; Investment analysis; eVal (Electronic resource)